E-learner satisfaction towards e-learning of higher education in Malaysia : a case study among students at UiTM Melaka City Campus / Siti Aminah Idris...[et al] - Idris, Siti Aminah (Faculty of Business and Management, 2012)
This study attempted to examine the e-Learner satisfaction towards e-Learning of higher education among the student in UiTM Melaka City Campus. The objectives of conducting this research are to identify the level of students' satisfaction towards eLearning (i-Learn) of higher learning education, determine the relationship between perceived usefulness with the perceived e-Learner satisfaction of higher learning education to determine the relationship between perceived ease of use with perceived e-Leaner satisfaction of higher learning education and also to determine the alternative way to increase e-Leaner satisfaction toward e-Leaning of higher learning education. A questionnaire was used as the main instrument for the purposed of data collection. This questionnaire consists of four different sections, demographic information , perceived usefulness of design approach toward e-Learner satisfaction , perceived ease of use of design approach toward e-Learner satisfaction and perceived student satisfaction toward e-Learning. The items in the questionnaire were constructed according to research objectives and research questions. The respondents of this research consist of students from UiTM Melaka City Campus.The data analyzed using the SPSS version 20.0. The Pearson Correlation Coefficient was used to detemine the relationship between perceived usefulness with perceivec e-Leaner satisfaction. The findings show a positive relationship between e-Leaner satisfactions and e-Learning. The findings also show a positive effect of user interface with perceived usefulness and ease of us. As a conclusion, eLearning systems important in the education medium and for the new generation students because they will get more benefit by using this system. The benefits students get by using this system include flexibility in terms of time and location.Researchers suggested that the management of the organization to provide speed of internet connection to the student. Furthermore, the organization also should provide more facilities to the students such as equipment, support service and even commitment on part of teaching to make the e-Leaner is satisfied with the system.